Systematic literature review: Learning geometry transformation using PMRI - Nizar, Harisman; Zulkardi, Zulkardi; Putri, Ratu Ilma Indra; Mulyono, Budi; Susanti, Ely (Program Studi Pendidikan Matematika, Universitas Islam Negeri Raden Fatah Palembang, 2025)
This study aims to conduct a systematic literature review related to geometric transformation learning using the Indonesian Realistic Mathematics Education (PMRI) approach. The research method employed was a Systematic Literature Review (SLR). The research data consisted of journal articles discussing PMRI-based geometric transformation learning. The article selection criteria included relevance to the research topic, publication in reputable journals, and alignment with PMRI principles. The results indicate that PMRI-based learning can improve students’ understanding of geometric transformation concepts through the use of realistic contexts. Therefore, PMRI can be considered an effective approach for teaching geometric transformation.